1983
DOI: 10.1136/bjo.67.8.546
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive exotropia following surgery.

Abstract: SUMMARY We studied 250 patients with consecutive exotropia. The interval between the surgical procedure and the onset of the consecutive exotropia may take many years. Consecutive exotropia occurred with all types of corrective esotropia surgery that we studied. Amblyopia and medial rectus limitation postoperatively seemed to be common factors associated with consecutive exotropia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
6
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 5 publications
1
31
6
2
Order By: Relevance
“…As is already known, the presence of amblyopia 8 and hypermetropia 9 are the most common risk factors for the development of consecutive exotropia and are also typical characteristics of most of the partially accommodative esotropia cases. Another risk factor for the development of consecutive exotropia is postoperative underaction of medial rectus 8 for which Resolution in partially accomodative esotropia F Koc et al high hypermetropic partially accommodative cases are also more prone with their smaller globe size. Although our 4-year follow-up period could be considered relatively short to draw these conclusions, this conservative approach might be a preventative factor for the development of consecutive exotropia.…”
Section: Discussionmentioning
confidence: 99%
“…As is already known, the presence of amblyopia 8 and hypermetropia 9 are the most common risk factors for the development of consecutive exotropia and are also typical characteristics of most of the partially accommodative esotropia cases. Another risk factor for the development of consecutive exotropia is postoperative underaction of medial rectus 8 for which Resolution in partially accomodative esotropia F Koc et al high hypermetropic partially accommodative cases are also more prone with their smaller globe size. Although our 4-year follow-up period could be considered relatively short to draw these conclusions, this conservative approach might be a preventative factor for the development of consecutive exotropia.…”
Section: Discussionmentioning
confidence: 99%
“…In our cases, it was noted that limitation of adduction was more frequent in the symmetrical rather than the asymmetrical surgical procedure. Amblyopia was reported as one of the important factors in the development of consecutive exotropia and the incidence was reported between 36–54.8% in different series [1, 9, 10]. It was proposed that amblyopia disturbing central binocular vision might cause consecutive exotropia after esotropia surgery [11].…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive exotropia secondary to esotropia surgery is rather frequent [1, 2]. Consecutive exotropia arising after surgery is an iatrogenic strabismus either due to inadequate diagnosis or inappropriate surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In our study we did not have patients with high degree of hyperopia witch according to some publication has been thought to be an important risk factor in producing a consecutive exotropia [2]. Amblyopia-another factor witch increase the risk of developing consecutive XT was found in 67.6% in our series.…”
Section: Discussionmentioning
confidence: 73%
“…This deviation occurs according to Von Noorden between 2% -8% [1] while other studies found an incidence ranged from 4% to 27% [2] [3]. This surgical complication can develop immediately after surgery or many years and even decades later [4] [5], some risk factors causing its development have been reported by ophthalmologist like high hyperopia, amblyopia, vertical deviation, A and V patterns, nystagmus, large medial rectus recessions, restriction of adduction, multiple surgeries, and developmental delay, the failure to evaluate the patient condition preoperatively [2] [3] [5]- [8].…”
Section: Introductionmentioning
confidence: 97%